An investigate of factors that influence intergration of Palliative care in state hospitals - Lazarus, Rebecca (Department of Public Health and Family Medicine, 2020)
Background: Palliative care (PC) is considered a necessary component of care that needs to be integrated into the South African health care system, including hospitals. In South Africa there has been a growth in legislation and policy frameworks stating the need for and promoting the development of hospital based PC programmes, however, how hospitals implement these policies is still unknown. Aim: The aim of this study was to identify factors that influence integration of PC in state hospitals and develop implementation recommendations. Objectives: The objectives of this study were (1) To describe existing PC services in three state hospitals in the Western Cape as perceived by the PC team; (2) To identify prohibiting and promoting factors in the integration of PC services in the three hospitals; and (3) To elicit views of health care professionals on how challenges to integrating PC in a hospital setting could be addressed. Method: This was a qualitative study whereby individual semi-structured interviews were conducted with 17 key informants (five-seven at each hospital). To obtain perspectives from relevant professionals on an operational and management level, key informants included chief executive officers, nursing managers, PC programme managers, physicians, nursing sisters, pharmacists, and social workers. The data was recorded, transcribed and analysed through steps of thematic analysis. Results: A description of each hospital’s PC programme was provided. Prohibiting factors identified most frequently related to resource challenges (insufficient human resources, time for PC, infrastructure and funding), followed by the hospital culture (limiting attitudes and beliefs about PC), education and training (limited opportunity, time and funding), health care providers (lack of PC knowledge, communication and hierarchy), as well as patient, family, community, and policy factors. Enabling factors identified were mainly related to having adequate resources (PC champions, effective teamwork, infrastructure and financial support). Raising awareness of PC needs and benefits (using practical methods), education and training in PC (formal and informal training opportunities), support structures (self-care, management and government support), partnerships (networking), and community-based support were also identified as promoting factors. Conclusion: Recommendations generated from this study were as follows: (1) Conduct a needs assessment to determine the organisations’ readiness and needs for PC integration; (2) Identify PC champions who have an interest in PC and influence in the organisation; (3) Raise PC awareness by providing education and training opportunities, and making PC part of the hospital culture; (4) Ensure adequate amount and use of human and material resources for PC; and (5) Network and build partnerships with other organisations who already have PC services.